Construction method and application of electrochemical luminescence antifouling sensor based on zwitter-ion hydrogel

By grafting SBMA onto BSA and encapsulating Au@luminol, an ECL anti-fouling sensor based on zwitterionic hydrogel was constructed, which solved the insufficient antifouling ability of the sensor in complex water environments. Problem, high sensitivity and long life trace detection is achieved.

CN119470400AActive Publication Date: 2025-02-18QINGDAO UNIV OF SCI & TECH

Patent Information

Application Number
CN202411391130.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-18
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

Existing electrochemiluminescence (ECL) sensors are difficult to maintain efficient anti-fouling capabilities in complex water environments, affecting their detection performance and service life.

Method used

A zwitterionic hydrogel was prepared as an antifouling interface by thiol-ene click reaction and Au@luminol was encapsulated in it. As an internal standard, an ECL anti-fouling sensor based on zwitterionic hydrogel was constructed.

Benefits of technology

This sensor combines the high hydrophilicity of hydrogels and the strong hydration of zwitterionic ions, significantly improves anti-fouling and antibacterial capabilities, enhances detection sensitivity and accuracy in complex water environments, and extends service life. The detection limit is as low as 0.39pM.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470400A_ABST
    Figure CN119470400A_ABST
Patent Text Reader

Abstract

The invention discloses a construction method and application of an electrochemical luminescence (ECL) antifouling sensor based on zwitter-ion hydrogel, and belongs to the technical fields of photoelectric sensing analysis, interface antifouling and environmental science. According to the invention, the hydrogel based on sulfobetaine methacrylate zwitterions and bovine serum albumin is used as the antifouling coating, so that the adsorption of biological proteins and bacteria is effectively hindered, and the service life of the sensor is prolonged. Meanwhile, the interior label Au (at) luminol is packaged in the antifouling hydrogel, so that the integration of interface antifouling and ratio detection is realized, the detection accuracy is improved, and the construction process of the ECL sensor is simplified. The constructed ECL anti-pollution sensor has high sensitivity to chloramphenicol detection, the detection limit is 0.39 pM, and the ECL anti-pollution sensor is suitable for trace detection of antibiotics in seawater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a construction method of an electrochemiluminescent antifouling sensor based on zwitterionic hydrogel and its application to chloramphenicol detection, belonging to the technical fields of photoelectric sensing analysis, interface antifouling and environmental science. Background Art

[0002] Chloramphenicol (CAP), as a common broad-spectrum antibiotic, is widely used to treat certain infectious diseases. However, excessive use of CAP can lead to water pollution, which affects human health. Electrochemiluminescence (ECL) has good application prospects in sensing analysis due to its advantages such as low background signal, simple operation mode and high sensitivity. Therefore, it is urgent to build a sensitive ECL sensing analysis platform for trace detection of CAP in water environment.

[0003] In complex water environments, in addition to the target analytes, there are other interfering substances that affect the detection performance and service life of the sensor through nonspecific adsorption. In order to solve the above problems, bovine serum albumin (BSA) is usually modified on the sensing interface to resist nonspecific adsorption. Although the BSA coating has good antifouling effect and biocompatibility, its inherent poor stability makes it difficult to maintain reliable antifouling ability in complex detection media. With the development of antifouling systems, many materials, such as polyethylene glycol, peptides, hydrogels and zwitterions, have been found to have antifouling properties. Among them, zwitterions have strong hydration ability and high stability, thus showing good inertness to changes in pH and salinity in aqueous solutions. At the same time, hydrogels with superhydrophilicity are also a reasonable choice for antifouling materials. Based on this, it is crucial to design an efficient and stable antifouling interface with the above excellent properties.

[0004] Based on this, the present invention grafted sulfobetaine methacrylate (SBMA) onto BSA through a thiol-ene click reaction, and developed a zwitterionic hydrogel as an antifouling interface, which combines the high hydrophilicity of the hydrogel and the strong hydration of the zwitterions, showing efficient antifouling and antibacterial capabilities. Compared with BSA, the developed zwitterionic hydrogel is more stable and suitable for sensitive detection of pollutants in complex water environments. In addition, Au@luminol is encapsulated in the zwitterionic antifouling gel as an internal standard, realizing the integration of interfacial antifouling and internal calibration, and providing a large number of active sites for the subsequent binding of biomolecules. With the introduction of antifouling and ratio strategies, the sensor constructed by the present invention has high detection sensitivity and accuracy, as well as high stability and long service life in complex water environments, thereby realizing trace detection of CAP, with a detection limit as low as 0.39pM, which provides help for the effective monitoring of antibiotic environmental pollutants in seawater. Summary of the invention

[0005] One of the technical tasks of the present invention is to make up for the deficiencies of the prior art, prepare a zwitterionic hydrogel as an antifouling interface for ECL sensing analysis, and improve the service life and specificity of the ECL sensor;

[0006] The second technical task of the present invention is to construct an ECL antifouling sensor based on zwitterionic hydrogel according to the interface antifouling and ratio detection strategy, which has high detection sensitivity and long service life, and the raw material cost is low, the preparation process is simple, and the operation is safe;

[0007] The third technical task of the present invention is to provide the use of the ECL antifouling sensor based on zwitterionic hydrogel constructed by the construction method, namely, for ultrasensitive detection of CAP in marine environment; the ECL antifouling sensor constructed by the present invention has a wide linear range, low detection limit and good specificity for CEA detection, can be used for effective monitoring of antibiotic environmental pollutants in seawater, and has certain industrialization prospects.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] 1. A method for constructing an electrochemiluminescent antifouling sensor based on zwitterionic hydrogel

[0010] The glassy carbon electrode was polished with Al2O3 powder to obtain a mirror-like surface; 4-6 μL of Au@luminol-SBMA-BSA hydrogel was modified on the pretreated glassy carbon electrode surface; the treated electrode was then immersed in a sodium salt solution of 4-(N-maleimidomethyl)cyclohexane-1-carboxylic acid sulfonic acid succinimide ester for crosslinking for 2 h; next, the electrode was incubated in a 10 μM H1 solution at 4°C for 2 h; the modified electrode was further incubated in a 10 μM H2-CdS solution for 2 h; finally, the obtained electrode was incubated in CAP solutions of different concentrations for 50 min to construct an ECL antifouling sensor based on zwitterionic hydrogel;

[0011] The Au@luminol-SBMA-BSA hydrogel is prepared by dissolving 80 mg of BSA in 20 mL of phosphate buffered saline solution, then adding 37.8 mg of NaBH4 and stirring for 30 min to reduce its disulfide bonds to thiol groups; then adding 2.24 g of SBMA monomer and irradiating under 365 nm ultraviolet light for 2 h to induce a thiol-ene click reaction; stirring the resulting solution overnight for polymerization, dialyzing the polymer product with a 14 KDa dialysis bag for 3 days, and freeze-drying to obtain SBMA-BSA; dissolving 8 mg of SBMA-BSA in 100 μL of ultrapure water, adding 20 μL of the prepared Au@luminol solution; and finally adding 5 μL of glutaraldehyde for cross-linking to obtain the Au@luminol-SBMA-BSA hydrogel;

[0012] The Au@luminol solution is prepared by heating 100 mL of HAuCl4 solution to boiling under stirring; quickly adding 1 mL of luminol to the solution, and keeping boiling for 30 minutes in the dark until the color of the solution changes from yellow to wine red; centrifuging the cooled solution at 10,000 rpm and washing 3 times; and redispersing the obtained precipitate in ultrapure water to obtain an Au@luminol solution;

[0013] The H2-CdS solution is prepared by dispersing 86 μL of mercaptopropionic acid in 20 mL of CdCl2 solution; adjusting the pH value of the mixed solution to 10 with 1 M NaOH, adding 20 mL of thioacetamide solution and stirring for 30 min; refluxing the mixture at 80° C. for 10 h, and dialyzing it in ultrapure water overnight; adding a mixed solution containing 0.1 M 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.01 M N-hydroxysuccinimide, and shaking it for 1 h to activate the carboxyl groups of CdS quantum dots; adding CAP aptamer H2, and incubating at 37° C. for 4 h to obtain the H2-CdS solution;

[0014] The CAP solutions of different concentrations are prepared by uniformly dispersing CAP at concentrations of 0 pM, 1 pM, 10 pM, 100 pM, 1 nM, 10 nM, and 100 nM in a phosphate buffered saline solution having a pH of 7.4 to obtain CAP solutions of different concentrations;

[0015] In each step of the electrode modification process, the modified electrode surface is gently rinsed with ultrapure water to remove incompletely bound reagents.

[0016] 2. The use of an electrochemiluminescent antifouling sensor based on zwitterionic hydrogel constructed by the construction method is used for the detection of broad-spectrum antibiotic CAP in marine environment. A phosphate buffered saline solution containing 0.1M K2S2O8 and 6.5mM H2O2 and a pH of 6.0-8.0 is used as the test solution, the constructed ECL sensor is immersed in the detection solution, and the ECL signal is tested using a three-electrode system including a working electrode, an auxiliary electrode and a reference electrode; the voltage applied during the experiment ranges from -1.6 to 0.8V, the amplification level is 3, and the photomultiplier tube high voltage is 600V; a linear curve is drawn based on the ECL response, and the detection range of the constructed ECL sensor is 1pM to 100nM, and the detection limit is as low as 0.39pM; the results show that the constructed ECL sensor has high stability, specificity and reproducibility, and is suitable for ultrasensitive detection of CAP in seawater.

[0017] Beneficial technical effects of the present invention:

[0018] 1. The present invention prepares a zwitterionic hydrogel as an antifouling interface for ECL sensing analysis; SBMA is grafted onto BSA using a thiol-ene click reaction, and the prepared antifouling sensing interface combines the high hydrophilicity of the hydrogel with the strong hydration of the zwitterions, showing efficient antifouling and antibacterial capabilities. Compared with BSA, the prepared zwitterionic antifouling gel is more stable and suitable for sensitive detection of pollutants in complex marine environments;

[0019] 2. The present invention constructs an ECL antifouling sensor based on zwitterionic hydrogel. By applying the interface antifouling and ratio detection strategy, the constructed ECL sensor has high detection sensitivity and precision, as well as a long working life, and the cost of the raw materials used is low, the preparation process is simple, and the operation is safe;

[0020] 3. The ECL antifouling sensor based on zwitterionic hydrogel constructed in the present invention exhibits a low detection limit and a wide linear range, a long working life, as well as high stability, specificity and reproducibility for the detection of CAP in seawater. It can be used for the effective monitoring of antibiotic pollutants in complex marine environments and has certain prospects for industrial application. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto, and all changes made to the technical solution of the present invention by professionals in this field should fall within the protection scope of the present invention.

[0022] Example 1 A method for constructing an electrochemiluminescent antifouling sensor based on zwitterionic hydrogels A glassy carbon electrode was polished with Al2O3 powder to obtain a mirror-like surface; 4 μL of Au@luminol-SBMA-BSA hydrogel was modified on the pretreated surface of the glassy carbon electrode; the treated electrode was then immersed in a sodium salt solution of 4-(N-maleimidomethyl)cyclohexane-1-carboxylic acid sulfonic acid succinimide ester for crosslinking for 2 h; next, the electrode was incubated in a 10 μM H1 solution at 4°C for 2 h; the modified electrode was further incubated in a 10 μM H2-CdS solution for 2 h; finally, the obtained electrode was incubated in CAP solutions of different concentrations for 50 min to construct an ECL antifouling sensor based on zwitterionic hydrogels;

[0023] The Au@luminol-SBMA-BSA hydrogel is prepared by dissolving 80 mg of BSA in 20 mL of phosphate buffered saline solution, then adding 37.8 mg of NaBH4 and stirring for 30 min to reduce its disulfide bonds to thiol groups; then adding 2.24 g of SBMA monomer and irradiating under 365 nm ultraviolet light for 2 h to induce a thiol-ene click reaction; stirring the resulting solution overnight for polymerization, dialyzing the polymer product with a 14 KDa dialysis bag for 3 days, and freeze-drying to obtain SBMA-BSA; dissolving 8 mg of SBMA-BSA in 100 μL of ultrapure water, adding 20 μL of the prepared Au@luminol solution; and finally adding 5 μL of glutaraldehyde for cross-linking to obtain the Au@luminol-SBMA-BSA hydrogel;

[0024] The Au@luminol solution is prepared by heating 100 mL of HAuCl4 solution to boiling under stirring; quickly adding 1 mL of luminol to the solution, and keeping boiling for 30 minutes in the dark until the color of the solution changes from yellow to wine red; centrifuging the cooled solution at 10,000 rpm and washing 3 times; and redispersing the obtained precipitate in ultrapure water to obtain an Au@luminol solution;

[0025] The H2-CdS solution is prepared by dispersing 86 μL of mercaptopropionic acid in 20 mL of CdCl2 solution; adjusting the pH value of the mixed solution to 10 with 1 M NaOH, adding 20 mL of thioacetamide solution and stirring for 30 min; refluxing the mixture at 80° C. for 10 h, and dialyzing it in ultrapure water overnight; adding a mixed solution containing 0.1 M 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.01 M N-hydroxysuccinimide, and shaking it for 1 h to activate the carboxyl groups of CdS quantum dots; adding CAP aptamer H2, and incubating at 37° C. for 4 h to obtain the H2-CdS solution;

[0026] The CAP solutions of different concentrations are prepared by uniformly dispersing CAP at concentrations of 0 pM, 1 pM, 10 pM, 100 pM, 1 nM, 10 nM, and 100 nM in a phosphate buffered saline solution having a pH of 7.4 to obtain CAP solutions of different concentrations;

[0027] In each step of the electrode modification process, the modified electrode surface is gently rinsed with ultrapure water to remove incompletely bound reagents.

[0028] Example 2 A method for constructing an electrochemiluminescent antifouling sensor based on zwitterionic hydrogels A glassy carbon electrode was polished with Al2O3 powder to obtain a mirror-like surface; 5 μL of Au@luminol-SBMA-BSA hydrogel was modified on the pretreated surface of the glassy carbon electrode; the treated electrode was then immersed in a sodium salt solution of 4-(N-maleimidomethyl)cyclohexane-1-carboxylic acid sulfonic acid succinimide ester for crosslinking for 2 h; next, the electrode was incubated in a 10 μM H1 solution at 4°C for 2 h; the modified electrode was further incubated in a 10 μM H2-CdS solution for 2 h; finally, the obtained electrode was incubated in CAP solutions of different concentrations for 50 min to construct an ECL antifouling sensor based on zwitterionic hydrogels;

[0029] The Au@luminol-SBMA-BSA hydrogel is prepared by dissolving 80 mg of BSA in 20 mL of phosphate buffered saline solution, then adding 37.8 mg of NaBH4 and stirring for 30 min to reduce its disulfide bonds to thiol groups; then adding 2.24 g of SBMA monomer and irradiating under 365 nm ultraviolet light for 2 h to induce a thiol-ene click reaction; stirring the resulting solution overnight for polymerization, dialyzing the polymer product with a 14 KDa dialysis bag for 3 days, and freeze-drying to obtain SBMA-BSA; dissolving 8 mg of SBMA-BSA in 100 μL of ultrapure water, adding 20 μL of the prepared Au@luminol solution; and finally adding 5 μL of glutaraldehyde for cross-linking to obtain the Au@luminol-SBMA-BSA hydrogel;

[0030] The Au@luminol solution is prepared by heating 100 mL of HAuCl4 solution to boiling under stirring; quickly adding 1 mL of luminol to the solution, and keeping boiling for 30 minutes in the dark until the color of the solution changes from yellow to wine red; centrifuging the cooled solution at 10,000 rpm and washing 3 times; and redispersing the obtained precipitate in ultrapure water to obtain an Au@luminol solution;

[0031] The H2-CdS solution is prepared by dispersing 86 μL of mercaptopropionic acid in 20 mL of CdCl2 solution; adjusting the pH value of the mixed solution to 10 with 1 M NaOH, adding 20 mL of thioacetamide solution and stirring for 30 min; refluxing the mixture at 80° C. for 10 h, and dialyzing it in ultrapure water overnight; adding a mixed solution containing 0.1 M 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.01 M N-hydroxysuccinimide, and shaking it for 1 h to activate the carboxyl groups of CdS quantum dots; adding CAP aptamer H2, and incubating at 37° C. for 4 h to obtain the H2-CdS solution;

[0032] The CAP solutions of different concentrations are prepared by uniformly dispersing CAP at concentrations of 0 pM, 1 pM, 10 pM, 100 pM, 1 nM, 10 nM, and 100 nM in a phosphate buffered saline solution having a pH of 7.4 to obtain CAP solutions of different concentrations;

[0033] In each step of the electrode modification process, the modified electrode surface is gently rinsed with ultrapure water to remove incompletely bound reagents.

[0034] Example 3 A method for constructing an electrochemiluminescent antifouling sensor based on zwitterionic hydrogels A glassy carbon electrode was polished with Al2O3 powder to obtain a mirror-like surface; 6 μL of Au@luminol-SBMA-BSA hydrogel was modified on the pretreated surface of the glassy carbon electrode; the treated electrode was then immersed in a sodium salt solution of 4-(N-maleimidomethyl)cyclohexane-1-carboxylic acid sulfonic acid succinimide ester for crosslinking for 2 h; next, the electrode was incubated in a 10 μM H1 solution at 4°C for 2 h; the modified electrode was further incubated in a 10 μM H2-CdS solution for 2 h; finally, the obtained electrode was incubated in CAP solutions of different concentrations for 50 min to construct an ECL antifouling sensor based on zwitterionic hydrogels;

[0035] The Au@luminol-SBMA-BSA hydrogel is prepared by dissolving 80 mg of BSA in 20 mL of phosphate buffered saline solution, then adding 37.8 mg of NaBH4 and stirring for 30 min to reduce its disulfide bonds to thiol groups; then adding 2.24 g of SBMA monomer and irradiating under 365 nm ultraviolet light for 2 h to induce a thiol-ene click reaction; stirring the resulting solution overnight for polymerization, dialyzing the polymer product with a 14 KDa dialysis bag for 3 days, and freeze-drying to obtain SBMA-BSA; dissolving 8 mg of SBMA-BSA in 100 μL of ultrapure water, adding 20 μL of the prepared Au@luminol solution; and finally adding 5 μL of glutaraldehyde for cross-linking to obtain the Au@luminol-SBMA-BSA hydrogel;

[0036] The Au@luminol solution is prepared by heating 100 mL of HAuCl4 solution to boiling under stirring; quickly adding 1 mL of luminol to the solution, and keeping boiling for 30 minutes in the dark until the color of the solution changes from yellow to wine red; centrifuging the cooled solution at 10,000 rpm and washing 3 times; and redispersing the obtained precipitate in ultrapure water to obtain an Au@luminol solution;

[0037] The H2-CdS solution is prepared by dispersing 86 μL of mercaptopropionic acid in 20 mL of CdCl2 solution; adjusting the pH value of the mixed solution to 10 with 1 M NaOH, adding 20 mL of thioacetamide solution and stirring for 30 min; refluxing the mixture at 80° C. for 10 h, and dialyzing it in ultrapure water overnight; adding a mixed solution containing 0.1 M 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.01 M N-hydroxysuccinimide, and shaking it for 1 h to activate the carboxyl groups of CdS quantum dots; adding CAP aptamer H2, and incubating at 37° C. for 4 h to obtain the H2-CdS solution;

[0038] The CAP solutions of different concentrations are prepared by uniformly dispersing CAP at concentrations of 0 pM, 1 pM, 10 pM, 100 pM, 1 nM, 10 nM, and 100 nM in a phosphate buffered saline solution having a pH of 7.4 to obtain CAP solutions of different concentrations;

[0039] In each step of the electrode modification process, the modified electrode surface is gently rinsed with ultrapure water to remove incompletely bound reagents.

[0040] Example 4 Use of the zwitterionic hydrogel-based electrochemiluminescent antifouling sensor constructed by the construction method described in Example 1, Example 2 and Example 3 for the detection of broad-spectrum antibiotic CAP in marine environments. A phosphate buffered saline solution containing 0.1M K2S2O8 and 6.5mM H2O2 and a pH of 6.0 is used as a test solution. The constructed ECL sensor is immersed in the detection solution, and an ECL signal test is performed using a three-electrode system comprising a working electrode, an auxiliary electrode and a reference electrode. The voltage range applied during the experiment is -1.6 to 0.8V, the amplification level is 3, and the photomultiplier tube high voltage is 600V. A linear curve is drawn based on the ECL response, and the detection range of the constructed ECL sensor is 1pM to 100nM, and the detection limit is as low as 0.39pM. The results show that the constructed ECL sensor has high stability, specificity and reproducibility, and is suitable for ultrasensitive detection of CAP in seawater.

[0041] Example 5 Use of the zwitterionic hydrogel-based electrochemiluminescent antifouling sensor constructed by the construction method described in Example 1, Example 2 and Example 3 for the detection of broad-spectrum antibiotic CAP in marine environments. A phosphate buffered saline solution containing 0.1 M K2S2O8 and 6.5 mM H2O2 and a pH of 7.0 is used as the test solution. The constructed ECL sensor is immersed in the detection solution, and the ECL signal is tested using a three-electrode system comprising a working electrode, an auxiliary electrode and a reference electrode. The voltage applied during the experiment ranges from -1.6 to 0.8 V, the amplification level is 3, and the photomultiplier tube high voltage is 600 V. A linear curve is drawn based on the ECL response, and the detection range of the constructed ECL sensor is 1 pM to 100 nM, and the detection limit is as low as 0.39 pM. The results show that the constructed ECL sensor has high stability, specificity and reproducibility, and is suitable for ultrasensitive detection of CAP in seawater.

[0042] Example 6 Use of the zwitterionic hydrogel-based electrochemiluminescent antifouling sensor constructed by the construction method described in Examples 1, 2 and 3 for the detection of broad-spectrum antibiotic CAP in marine environments. A phosphate buffered saline solution containing 0.1 M K2S2O8 and 6.5 mM H2O2 and a pH of 8.0 is used as the test solution. The constructed ECL sensor is immersed in the detection solution, and the ECL signal is tested using a three-electrode system comprising a working electrode, an auxiliary electrode and a reference electrode. The voltage applied during the experiment ranges from -1.6 to 0.8 V, the amplification level is 3, and the photomultiplier tube high voltage is 600 V. A linear curve is drawn based on the ECL response, and the detection range of the constructed ECL sensor is 1 pM to 100 nM, and the detection limit is as low as 0.39 pM. The results show that the constructed ECL sensor has high stability, specificity and reproducibility, and is suitable for ultrasensitive detection of CAP in seawater. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Flow chart of the construction method of ECL antifouling sensor based on zwitterionic hydrogel (glassy carbon electrode: GCE; reduced bovine serum albumin: re-BSA; glutaraldehyde: GA; complementary chain: H1; chloramphenicol aptamer chain: H2).

[0044] Figure 2 Infrared spectra of BSA, SBMA and BSA@PSBMA.

[0045] Figure 3 X-ray photoelectron spectrum of BSA@PSBMA, including: (A) full-area X-ray photoelectron spectrum of BSA@PSBMA; (B) high-resolution X-ray photoelectron spectrum of N 1s region; (C) high-resolution X-ray photoelectron spectrum of S2p region.

[0046] Figure 4 Transmission electron microscopy images of (A) Au@luminol and (B) CdS quantum dots.

[0047] Figure 5 UV-visible absorption spectra of (A) Au NPs (black curve), luminol (red curve), Au@luminol (blue curve), and (B) CdS quantum dots.

[0048] Figure 6 Scanning electron microscope image and corresponding element mapping of Au@luminol-BSA@PSBMA hydrogel.

[0049] Figure 7 This is the rheological measurement results of Au@luminol-BSA@PSBMA hydrogel.

[0050] Figure 8 Static water contact angle diagrams of (A) GCE, (B) BSA hydrogel / GCE and (C) Au@luminol-BSA@PSBMA hydrogel / GCE.

[0051] Fig. 9 Static water contact angle bar graphs of BSA hydrogel / GCE and Au@luminol-BSA@PSBMA hydrogel / GCE in different (A) pH and (B) ionic salts.

[0052] Fig.10 The diagram shows the condition optimization of the ECL antifouling sensor based on zwitterionic hydrogel, including: (A) contact angle optimization result diagram; (B) CAP incubation time optimization result diagram.

[0053] Fig.11 Differential pulse voltammetry curves of (A) GCE and (B) Au@luminol-BSA@PSBMA hydrogel / GCE incubated in different concentrations of fetal bovine serum.

[0054] Fig.12 (A) Fluorescence imaging of ITO, BSA hydrogel / ITO and Au@luminol-BSA@PSBMA hydrogel / ITO after incubation in fluorescein-conjugated BSA solution and (B) the corresponding fluorescence quantitative analysis graph.

[0055] Fig.13 (A) Fluorescence imaging of ITO, BSA hydrogel / ITO and Au@luminol-BSA@PSBMA hydrogel / ITO after incubation in E. coli solution and (B) the corresponding fluorescence quantitative analysis graph.

[0056] Fig.14Characterization diagram of the construction process of zwitterionic hydrogel-based ECL antifouling sensor according to (A) differential pulse voltammetry and (B) electrochemical impedance spectroscopy tests.

[0057] Fig.15 For GCE, Au@luminol-BSA@PSBMA / GCE, H2-CdS / H1 / Au@luminol-BSA@PSBMA / GCE, and CAP / H2-CdS / H1 / Au@luminol-BSA@PSBMA / GCE in the presence of 0.1 M S2O8 2- ECL curves in phosphate buffered saline with 6.5 mM H2O2.

[0058] Fig.16 (A) ECL curve diagram and (B) corresponding calibration curve diagram of the ECL antifouling sensor based on zwitterionic hydrogel after incubation with different concentrations of CAP; wherein, a to g represent the concentrations of 0pM, 1pM, 10pM, 100pM, 1nM, 10nM, and 100nM, respectively.

[0059] Fig.17 (A) specificity, (B) signal stability, (C) reproducibility, and (D) storage stability of the ECL antifouling sensor based on zwitterionic hydrogel.

Claims

1. A method for constructing an electrochemiluminescent antifouling sensor based on zwitterionic hydrogel, characterized in that: The glassy carbon electrode was polished with Al2O3 powder to obtain a mirror-like surface; 4-6 μL of Au@luminol-methacrylic acid sulfobetaine zwitterion-bovine serum albumin hydrogel was modified on the pretreated glassy carbon electrode surface; the treated electrode was then immersed in a sodium salt solution of 4-(N-maleimidomethyl)cyclohexane-1-carboxylic acid sulfonyl succinimide ester for crosslinking for 2 h; Next, the electrode was incubated in a 10 μM H1 solution at 4 °C for 2 h; the modified electrode was further incubated in a 10 μM H2-CdS solution for 2 h; finally, the obtained electrode was incubated in chloramphenicol solutions of different concentrations for 50 min to construct an electrochemiluminescent antifouling sensor based on zwitterionic hydrogels.

2. The method for constructing an electrochemiluminescent antifouling sensor based on zwitterionic hydrogel according to claim 1, characterized in that: The Au@luminol-methacrylic acid sulfobetaine zwitterion-bovine serum albumin hydrogel is prepared by dissolving 80 mg of bovine serum albumin in 20 mL of phosphate buffered saline solution, then adding 37.8 mg of NaBH4 and stirring for 30 min to reduce its disulfide bonds to thiol groups; then adding 2.24 g of methacrylic acid sulfobetaine monomer and irradiating under 365 nm ultraviolet light for 2 h to induce a thiol-ene click reaction; stirring the resulting solution overnight for polymerization, dialyzing the polymerization product with a 14 KDa dialysis bag for 3 days, and freeze-drying to obtain methacrylic acid sulfobetaine zwitterion-bovine serum albumin; dissolving 8 mg of methacrylic acid sulfobetaine zwitterion-bovine serum albumin in 100 μL of ultrapure water, adding 20 μL of the prepared Au@luminol solution; and finally adding 5 μL of glutaraldehyde for cross-linking to obtain the Au@luminol-methacrylic acid sulfobetaine zwitterion-bovine serum albumin hydrogel.

3. The method for constructing an electrochemiluminescent antifouling sensor based on zwitterionic hydrogel according to claim 2, characterized in that: The Au@luminol solution is prepared by heating 100 mL of HAuCl4 solution to boiling under stirring; quickly adding 1 mL of luminol to the solution, and keeping boiling for 30 minutes in the dark until the color of the solution changes from yellow to wine red; centrifuging the cooled solution at 10,000 rpm and washing 3 times; and redispersing the obtained precipitate in ultrapure water to obtain the Au@luminol solution.

4. The method for constructing an electrochemiluminescent antifouling sensor based on zwitterionic hydrogel according to claim 1, characterized in that: The H2-CdS solution is prepared by dispersing 86 μL of mercaptopropionic acid in 20 mL of CdCl2 solution; adjusting the pH value of the mixed solution to 10 with 1 M NaOH, adding 20 mL of thioacetamide solution and stirring for 30 min; refluxing the mixture at 80° C. for 10 h, and dialyzing it in ultrapure water overnight; adding a mixed solution containing 0.1 M 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.01 M N-hydroxysuccinimide, and shaking it for 1 h to activate the carboxyl groups of CdS quantum dots; adding chloramphenicol aptamer H2, and incubating it at 37° C. for 4 h to obtain the H2-CdS solution.

5. The method for constructing an electrochemiluminescent antifouling sensor based on zwitterionic hydrogel according to claim 1, characterized in that: The chloramphenicol solutions of different concentrations are obtained by uniformly dispersing chloramphenicol at concentrations of 0pM, 1pM, 10pM, 100pM, 1nM, 10nM and 100nM in a phosphate buffered saline solution with a pH of 7.

4.

6. The method for constructing an electrochemiluminescent antifouling sensor based on zwitterionic hydrogel according to claim 1, characterized in that: In each step of the electrode modification process, the modified electrode surface is gently rinsed with ultrapure water to remove incompletely bound reagents.

7. Use of an electrochemiluminescent antifouling sensor based on zwitterionic hydrogel constructed by the construction method according to claim 1 for the detection of chloramphenicol.

Citation Information

Patent Citations

  • N-(4-aminobutyl)-N-ethylisoluminol luminescence functionalized nanogold, and preparation method and application thereof

    CN102191034A

  • Method for preparing electrochemical luminescence sensor made of nano-composites

    CN105115961A

  • Polysulfobetaine-encapsulated protein nano-microcapsules and preparation method thereof

    CN110917171A

  • Preparation method of electrochemical luminescence sensor for detecting cadmium and ampicillin in aquatic products

    CN115356383A

  • Nano-bubble enhanced luminol electrochemical luminescence sensor, preparation method thereof and application of nano-bubble enhanced luminol electrochemical luminescence sensor in chloramphenicol detection

    CN116818862A

Cited By

  • Construction method and application of electrochemical luminescence biosensor based on cell membrane hydrogel antifouling interface

    CN120446225A

  • Construction method and application of an electrochemiluminescence biosensor based on cell membrane hydrogel antifouling interface

    CN120446225B

  • Construction and application of electrochemical luminescence sensor based on oxygen evolution reaction and self-supporting electrode

    CN120741439A

  • Construction and application of bifunctional biosensor based on coordination induced enhancement and interface antifouling

    CN121453874A